Determining the height of deep volcanic eruptions over the tropical western Pacific with Himawari-8 - Chris Lucas (Journal of Southern Hemisphere Earth Systems Science, 2023)
Volcanic eruptions are significant aviation hazards due to the formation of airborne volcanic ash clouds. Further, deep eruptions that reach the upper troposphere and lower stratosphere may have significant weather and climate impacts. A key variable for both dispersion model forecasting for aviation hazards and understanding climate impacts is the volcanic plume height. This work presents a method to quickly and reliably estimate the maximum plume heights of volcanic eruptions that interact with the tropical tropopause layer in the tropical western Pacific region. The method uses infrared (11.2μm) data from Himawari-8 to identify ‘stratospheric warm spots’ in optically thick portions of the eruption cloud top by searching for reversals in the local-brightness temperature gradient. The brightness temperature of these warm spots is converted to height using seasonal stratospheric reference temperature profiles derived from 20years of radiosonde data from 17 stations spread throughout the western Pacific. An approach for estimating the height of cold ‘overshooting tops’ is also adopted. Based on the radiosonde data, estimates of the uncertainty in the plume height depend on the height and range within 0.5–5.0km. A case study of the 19 December 2021 eruption of Hunga Tonga-Hunga Ha’apai demonstrates the technique. The heights are robustly determined with this simple technique and compare well with height estimates of eruptions in the literature that use more complex satellite techniques.